2003
DOI: 10.1063/1.1497835
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized pore formation and open-loop control in semiconductor etching

Abstract: Electrochemical etching of semiconductors, apart from many technical applications, provides an interesting experimental setup for self-organized structure formation capable e.g. of regular, diameter-modulated, and branching pores. The underlying dynamical processes governing current transfer and structure formation are described by the CurrentBurst-Model: all dissolution processes are assumed to occur inhomogeneously in time and space as a Current Burst (CB); the properties and interactions between CB's are de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
(39 reference statements)
2
12
0
Order By: Relevance
“…Among the first porous domains were the ones observed in anodically etched GaP and described in detail by Erne et al 19 The present paper reports other distinct domain types observed in Ge, GaAs, and InP. No domain formation had been observed in Si until the recent discovery of the rather exotic "fractal" pores 22 which form clear surface domains. The aim of this paper is to discuss the etching conditions, the mechanism of domain formation, and the most common and uncommon features by comparing different types of domains.…”
supporting
confidence: 63%
“…Among the first porous domains were the ones observed in anodically etched GaP and described in detail by Erne et al 19 The present paper reports other distinct domain types observed in Ge, GaAs, and InP. No domain formation had been observed in Si until the recent discovery of the rather exotic "fractal" pores 22 which form clear surface domains. The aim of this paper is to discuss the etching conditions, the mechanism of domain formation, and the most common and uncommon features by comparing different types of domains.…”
supporting
confidence: 63%
“…Due to a locally enhanced field around sharp structures, originally small pores closely neighboring to a prestructured nucleus can be bundled and pressed together into the predefined site and thus a larger pore forms. This can be understood as a phase separation mechanism of pores, as addressed in CBM [19,24] : due to the strengthened interactions (induced by localized field enhancement) between local CBs, the prestructured nuclei gather much more electric-field lines (and thus CBs) and attract the highest current density while rendering the other parts (outside the nuclei) totally inert. Note that in this work all anodizations were performed without any mask (i.e.…”
Section: The Dissimilar Evolution Of Pore Densities On Patterned and mentioning
confidence: 99%
“…Electric-field effect as well as current-burst-model (CBM) was employed to interpret the underlying mechanism. electrochemistry, surface morphology, patterned and unpatterned specimen, physical and chemical factor, I-V (current-voltage) curveConcerning porous silicon (PS) formation, numerous work with respect to SCR (space charge region) effects [1][2][3][4][5][6] , electrochemical oxidation [7,8] , hydrogen passivation or incorporation [9,10] , breakdown mechanism [11,12] , diffusion-limited random walk [13,14] , surface instabilities [15][16][17] , current bursts [18,19] , geometry relativity [20,21] , solvent effects [22] , etc. [23][24][25] , has been advanced.…”
mentioning
confidence: 99%
“…31 where an amplitude modulation of the pore etching current with a frequency of around 33 mHz showed a large effect whereas other frequencies did not noticeably change the pore geometry Generally, given the non-linear nature of the CB model, one might expect that superimposed periodic external disturbances at frequencies that scale with the internal (CB) frequencies of the system might produce strong non-linear effects.…”
Section: Modeling the Growth Of Crystallographic Pores In Inp Andmentioning
confidence: 99%